OS08.8.A Integrin-specific CAR T cells for the treatment of glioblastoma. (5th September 2022) - Villars, D; Hänsch, L; Silginer, M; Weiss, T; Weller, M; Roth, P
Abstract: Background: Current standard of care for glioblastoma patients has limited therapeutic efficacy and novel innovative treatment strategies are urgently needed. One such strategy is chimeric antigen receptor (CAR) T cell therapy that has shown great success in hematological malignancies. αv integrins are overexpressed in several neoplasms and have already been used as therapeutic targets for small molecule inhibitors and antibodies, which did not cause major toxicities. Herein, we propose αv integrins as an ideal target for CAR T cell therapy in glioblastoma. Material and Methods: CAR T cells targeting specific heterodimers (αvβ3, αvβ5 or αvβ8) were generated by transducing primary human T cells from healthy donors with a lentiviral vector expressing a second-generation CAR. Activity and specificity of CAR T cells was determined by co-culture assays with different glioma cells. Efficacy of CAR T cells to control tumor growth in vivo was investigated in clinically relevant orthotopic xenograft glioma mouse models. Additionally, we generated CAR T cells from T cells from a glioblastoma patient and measured their activity against the patient's autologous tumor cells. Results: All newly generated integrin-targeting CAR T cells exerted strong anti-glioma activity in vitro . Long-term and repetitive killing assays as well as cytokine-release measurements demonstrated highest activity of αvβ5 and αvβ8 integrin-specific CAR T cells. Antigen specificity of these cells was confirmed, as glioma cells with a CRISPR/Cas9-mediated knockout of the target antigen were resistant to CAR T cell-mediated cytotoxicity. Intratumoral injection of αvβ5 or αvβ8 CAR T cells significantly prolonged the survival and cured a substantial fraction of glioma-bearing mice in two different xenograft models. When used in a patient-derived setting, matched CAR T cells exerted strong anti-glioma activity. Conclusion: We show strong and integrin-specific anti-glioma activity of CAR T cells developed from healthy donor T cells and glioblastoma-patient-derived T cells in vitro . αvβ5- and αvβ8-specific CAR T cells exerted the best therapeutic activity in two different xenograft glioma models in vivo . These data support the evaluation of integrin-specific CAR T cells as a therapeutic strategy in clinical neuro-oncology.